Estudo de perdas técnicas de energia elétrica em sistemas de distribuição - Moritz, Vinicius Fernando (2016)
This work presents a study about technical losses of eletrical energy in distribution systems. Such losses are inherent to the process, that is, are originate from the Joule effect, Conora effect, leakage currents, losses in the cores of transformers, among other losses. In this sense, research on these losses will be performed in order to identify them and observe their behavior. For this, will be used some mathematical models proposed in the literature for the calculation of technical losses in distribution systems, which have been developed and adjusted to calculate technical losses using different types of information available at the dealerships. These models will be implemented in MATLAB software for the calculation of technical losses in two feeders located in the same substation, belonging to a real distribution system. The feeders will be implemented in SimPowerSystems of MATLAB, in the sense of simulate these technical losses so that, posteriorly, the results obtained through mathematical models are compared with the data found in the simulation. Thereby, is desired to verify the validity of mathematical models.